Effects of addition of Trichoderma spp. on growth and soil microorganisms of continuously cropped Salvia miltiorrhiza - Zhang, Linlin; Pan, Xiaoxi; Zhang, Yue; Guan, Yiming; Li, Yincun; Jin, Qiao; Cao, Keming; Shan, Chenggang; Wang, Qiuxia (Frontiers in Plant Science, 2025)
IntroductionContinuous cropping (CC) poses significant challenges to the yield and quality of Salvia miltiorrhiza, a medicinally important plant with annual market demand of around 20 million kg. Previous studies have explored chemical mitigation methods, but concerns persist regarding environmental pollution and safety issues.MethodsIn this study, we evaluated three strains of the fungus Trichoderma (T. brevicompactum, T. viridescens, and T. velutinum) as ecofriendly alternatives for CC obstacle mitigation in S. miltiorrhiza cultivation.ResultsThe Trichoderma treatments significantly enhanced the relative abundance of beneficial soil bacteria (Actinobacteria 9.25%–16.88%; Chloroflexi 6.41%–16.73%; Gemmatimonadetes 1.21%–3.16%), while decreasing the abundance of pathogenic Fusarium by 12.67%–31.75%. Soil analysis revealed substantial improvements in total organic carbon (47.35%–65.88%), nitrate nitrogen (91.38%–318.89%), available potassium (4.29%–17.16%), and available phosphorus (1.85%–11.86%) following Trichoderma treatment. T. brevicompactum demonstrated superior performance among the three tested strains, increasing the individual plant fresh weight by 17.79% and the survival rate by 13.33%. This treatment also significantly elevated (p < 0.05) the content of key bioactive compounds in S. miltiorrhiza root: tanshinone IIA (51.16% increase), cryptotanshinone (56.76%), tanshinone I (50.00%), and salvianolic acid B (18.43%).DiscussionTrichoderma can effectively alleviate S. miltiorrhiza CC obstacles by improving the soil nutrient status and modulating the soil microbial community, thereby enhancing plant growth and stress resistance. This study provides a promising ecofriendly strategy for sustainable cultivation of S. miltiorrhiza and other medicinal plants facing similar challenges.